Integrated licensing policy with electronic policy:study in the department of capital investment and integrated services Of jember indonesia - Audyna, Nadya; Wicaksono, Itok (POLITICO, 2019)
Electronic Integrated Licensing Services or Online Single Submission, hereinafter abbreviated as OSS, are Business Licenses issued by OSS Institutions for and on behalf of ministers, heads of institutions, governors, or regents/mayors to business actors through integrated electronic systems. Jember Regency as one of the Regencies that have implemented OSS,began to implement it in 2018. This service is a government effort to simplify business licensing and create an integrated licensing service model that is fast, inexpensive and certain. In this study the researchers used the Edward III Theory of communication, bureaucratic structure, disposition and resources. The results of this study show that Jember?sInvestment and Integrated One-Stop Service is not yet optimal in carrying out its duties, because in the bureaucratic structure no SOP for this policy resulting in overlapping responsibilities because the organizers are responsible for serving Single Online services Submission (OSS) also serves services manually. In addition, even though the Jember regency government has conducted licensing related online, there are still many people and business people from those who are processing the permits to the One Stop Integrated Investment and Service Office of Jember Regency.